AMP-Activated Protein Kinase Mediates the Effect of Leptin on Avian Autophagy in a Tissue-Specific Manner - Piekarski, Alissa; Nagarajan, Gurueswar; Ishola, Peter; Flees, Joshua; Greene, Elizabeth S.; Kuenzel, Wayne J.; Ohkubo, Takeshi; Maier, Helena; Bottje, Walter G.; Cline, Mark A.; Dridi, Sami (Frontiers in Physiology, 2018)
Autophagy, a highly conserved intracellular self-eating process, plays an integral role in maintaining cellular homeostasis. Although emerging evidence indicate that the endocrine system regulates autophagy in mammals, there is still a paucity of information on autophagy in avian (non-mammalian) species. Here, we show that intracerebroventricular administration of leptin reduces feed intake, modulates the expression of feeding-related hypothalamic neuropeptides, activates leptin receptor and signal transducer and activator of transcription (Ob-Rb/STAT) pathway, and significantly increases the expression of autophagy-related proteins (Atg3, Atg5, Atg7, beclin1, and LC3B) in chicken hypothalamus, liver, and muscle. Similarly, leptin treatment activates Ob-Rb/STAT pathway and increased the expression of autophagy-related markers in chicken hypothalamic organotypic cultures, muscle (QM7) and hepatocyte (Sim-CEL) cell cultures as well as in Chinese Hamster Ovary (CHO-K1) cells-overexpressing chicken Ob-Rb and STAT3. To define the downstream mediator(s) of leptin’s effects on autophagy, we determined the role of the master energy sensor AMP-activated protein kinase (AMPK). Leptin treatment significantly increased the phosphorylated levels of AMPKα1/2 at Thr172 site in chicken hypothalamus and liver, but not in muscle. Likewise, AMPKα1/2 was activated by leptin in chicken hypothalamic organotypic culture and Sim-CEL, but not in QM7 cells. Blocking AMPK activity by compound C reverses the autophagy-inducing effect of leptin. Together, these findings indicate that AMPK mediates the effect of leptin on chicken autophagy in a tissue-specific manner.